A Structured Pre- and Post-Operative Voice Therapy Program for Benign Vocal Fold Lesions - Juliana Codino; Erik McLeod Christensen (Revista de Investigación e Innovación en Ciencias de la Salud, 2023)
Benign vocal fold lesions (BVFLs) are acquired structural anomalies of the vocal folds, and these are primarily a result of vocal abuse or phonotrauma. Phonotraumatic lesions are not generally regarded as recurrent, provided that appropriate behavioral changes are made after resolution or surgical removal. Voice therapy plays a crucial role in this aspect. The aim of this article is to propose a structured pre- and post-operative voice therapy program for patients undergoing surgical intervention for BVFLs. Voice therapy post-surgery has been proven to reduce the rate of recurrence in BVFLs. Having a standard treatment protocol is a useful tool for the therapist, particularly one without extensive voice training.